A Precision Medicine Approach to the Rescue of Function on Malignant Calmodulinopathic Long-QT Syndrome. Issue 1 (6th January 2017) - Limpitikul, Worawan B.; Dick, Ivy E.; Tester, David J.; Boczek, Nicole J.; Limphong, Pattraranee; Yang, Wanjun; Choi, Myoung Hyun; Babich, Jennifer; DiSilvestre, Deborah; Kanter, Ronald J.; Tomaselli, Gordon F.; Ackerman, Michael J.; et al.
Abstract : Rationale: : Calmodulinopathies comprise a new category of potentially life-threatening genetic arrhythmia syndromes capable of producing severe long-QT syndrome (LQTS) with mutations involving CALM1, CALM2, or CALM3 . The underlying basis of this form of LQTS is a disruption of Ca 2+ /calmodulin (CaM)-dependent inactivation of L-type Ca 2+ channels. Objective: : To gain insight into the mechanistic underpinnings of calmodulinopathies and devise new therapeutic strategies for the treatment of this form of LQTS. Methods and Results: : We generated and characterized the functional properties of induced pluripotent stem cell–derived cardiomyocytes from a patient with D130G- CALM2 –mediated LQTS, thus creating a platform with which to devise and test novel therapeutic strategies. The patient-derived induced pluripotent stem cell–derived cardiomyocytes display (1) significantly prolonged action potentials, (2) disrupted Ca 2+ cycling properties, and (3) diminished Ca 2+ /CaM-dependent inactivation of L-type Ca 2+ channels. Next, taking advantage of the fact that calmodulinopathy patients harbor a mutation in only 1 of 6 redundant CaM-encoding alleles, we devised a strategy using CRISPR interference to selectively suppress the mutant gene while sparing the wild-type counterparts. Indeed, suppression of CALM2 expression produced a functional rescue in induced pluripotent stem cell–derived cardiomyocytes with D130G- CALM2, as shown by the normalization of action potential duration and Ca 2+ /CaM-dependent inactivation after treatment. Moreover, CRISPR interference can be designed to achieve selective knockdown of any of the 3 CALM genes, making it a generalizable therapeutic strategy for any calmodulinopathy. Conclusions: : Overall, this therapeutic strategy holds great promise for calmodulinopathy patients as it represents a generalizable intervention capable of specifically altering CaM expression and potentially attenuating LQTS-triggered cardiac events, thus initiating a path toward precision medicine. Abstract : Supplemental Digital Content is available in the text.